Electronic word-of-mouth generation and regulatory focus. Issue 1 (22nd June 2019) - Sohaib, Muhammad; Akram, Umair; Hui, Peng; Rasool, Hassan; Razzaq, Zohaib; Kaleem Khan, Muhammad
Abstract : Purpose: The purpose of this paper is to investigate the electronic word-of-mouth (eWOM) motivations of regulatory-focused customers with positive and negative consumption experiences. Design/methodology/approach: An online survey is conducted in Beijing and Shanghai. A random sampling technique is used to collect data from 854 respondents. Two scenarios of eWOM communication – positive and negative consumption experiences – are randomly assigned to each respondent. This study employs the structural equation modeling and confirmatory factor analysis techniques. However, it uses ordinary least squares and logistic regression to analyze 137 participants in the experimental study. Findings: Promotion-focused customers that aim for self-enhancement and obtaining social benefits are motivated to spread positive eWOM on social networking sites. However, prevention-focused customers are driven by vengeance and anxiety, revealing higher intentions to post negative eWOM on review sites. eWOM generation is subject to gender, as promotion-focused male customers spread it more than both prevention-focused and promotion-focused female customers. Moreover, platform assistance (PA) has a significant positive impact upon regulatory-focused customers and eWOM (positive vs negative) relationships. Practical implications: This study provides a deeper understanding of motivational factors of eWOM communication. Specifically, in case of product or service failure, negative consumption experiences drive prevention-focused customers to generate negative eWOM. Thus, using various tactics, marketers need to shift customers from focusing on prevention to focusing on promotion. For example, redeemable free coupons can shift customer attention and generate positive eWOM. Originality/value: This study provides unique insights about eWOM motivation across genders. It examines regulatory focus, positive vs negative consumption experiences and moderation of PA.